Biochemical, endocrine, and histopathological profile of liver and kidneys of sheep with pregnancy toxemia - Rodolfo J.C. Souto; José A.B. Afonso; Carla L. Mendonça; Antônio Flávio M. Dantas; Jobson F.P. Cajueiro; Daniel N.A. Gonçalves; Emanuel F. Olivera Filho; Pierre C. Soares (Pesquisa Veterinária Brasileira, 2019)
ABSTRACT: The objective of the present study was to characterize the biochemical, hormonal, and mineral profile, and histopathology of the liver and kidneys, related to the severity of natural cases of pregnancy toxemia (PT) in sheep. A total of 45 sheep with PT were analyzed at the “Clínica de Bovinos”, Campus Garanhuns-UFRPE. The animals were submitted to clinical examination, followed by the collection of blood and urine. A necropsy was performed on thirteen animals that died and a histopathological examination was performed on samples of liver and kidneys. Increased creatinine, urea, glucose, fructosamine, non-esterified fatty acids, β-hydroxybutyrate, cortisol, chlorine, amylase, aspartate aminotransferase, gamma-glutamyltransferase, and folic acid were found, whereas insulin, potassium, and total and ionizable calcium presented low values for the species. Total protein, albumin, globulin, sodium, magnesium, and vitamin B12 remained within the normal range. In the macroscopic analysis of the liver, it was possible to observe an increase in organ and border size, yellowish coloration and parenchyma that varied from firm to friable. Vacuolation of the hepatocytes and renal tubular cells was observed. Metabolic disorders in sheep associated with hepatic and renal lesions are more apparent in overweight animals. With the greater impairment in hepatic and renal function, the clinical prognosis of animals with a high body score should be considered reserved.